Extracorporeal Shockwave Therapy for Calcified Tendinopathy of Supraspinatus: A Case Report - Gautam, Madan; Yadav, Manoj Kumar; Khadka, Ajay; Khadka, Anjan (Medical Journal of Shree Birendra Hospital, 2025)
Calcified tendinopathy of the supraspinatus, an enthesopathy caused by calcium phosphate crystal deposition, typically develops 1.5–2 cm from the tendon insertion and is common in individuals aged 30–50, particularly women. We present a case of a 60-year-old female with a 3-month history of dull, insidious right shoulder pain radiating to the arm, worsened by overhead activity and associated with night pain and weakness. Pain was localized to the anterior and lateral shoulder. After nine ineffective physiotherapy sessions and medication, extracorporeal shock wave therapy (ESWT) was administered. ESWT proved to be a safe and effective treatment, significantly improving pain and function.